1999
DOI: 10.1136/pgmj.75.888.617
|View full text |Cite
|
Sign up to set email alerts
|

Follicular carcinoma in a functioning struma ovarii

Abstract: We describe a case of follicular carcinoma in a functioning struma ovarii, which presented as an ovarian mass in a patient who had undergone a near-total thyroidectomy for a benign lesion. She underwent bilateral salpingo-oophorectomy and received radiotherapy and L-thyroxine treatment with no evidence of metastases in 4 years follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…8,9 Previous reports have shown that patients with struma ovarii are largely without symptoms, or are accompanied by non-specific symptoms that are similar to other ovarian neoplasms. 10 The results of this study seem to be in agreement with the above observations as demonstrated by the fact that in 14 of the 34 patients, there were no presenting symptoms, and the tumors were discovered during routine check-up ultrasound studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Previous reports have shown that patients with struma ovarii are largely without symptoms, or are accompanied by non-specific symptoms that are similar to other ovarian neoplasms. 10 The results of this study seem to be in agreement with the above observations as demonstrated by the fact that in 14 of the 34 patients, there were no presenting symptoms, and the tumors were discovered during routine check-up ultrasound studies.…”
Section: Discussionmentioning
confidence: 99%
“…8,16 Distant metastasis has been reported to be a very uncommon feature of struma ovarii, and even if present, has a protracted course. An extreme case where distant metastasis was discovered 26 years after initial diagnosis has been reported.…”
Section: 13mentioning
confidence: 99%
“…However, strumae with follicular, anaplastic and Hürthle cell thyroid carcinoma have also been described [7,8,21]. The left ovary appears to be more frequently involved in struma ovarii than the right and in 6% of instances strumae ovarii are bilateral [16].…”
Section: Discussionmentioning
confidence: 99%
“…Although 5%-15% of all ovarian teratomas may contain some thyroid tissue, only 2% of these are made exclusively of struma ovarii. About 5% of all struma ovarii are malignant (1). We report the case of a malignant struma ovarii that presented with disseminated lung metastases 4 years after ablation of the ovarian tumor.…”
Section: Introductionmentioning
confidence: 95%